Effects of lighting levels on the study tasks of selected college students in boarding houses in Krus na Ligas - Tungpalan, Danielle Christine R.; Bautista, Avigail Vergara (2009.)
This case study aimed to identify the effects of how lighting levels on study tasks of students on boarding houses within a university area. The study used a descriptive method and computational analysis of lighting levels in selected rented rooms. A Non-Probability sampling design was used for the forty students chosen in the study. A record sheet of the documentation of the physical features of the rooms and a user-evaluation questionnaire were used to gather information. The comparison of existing lighting conditions to the general lighting standards was then accomplished by using the derived formula from Rooney's standards and IES Illuminance Category from Kaufman's 1984 volume edition. The findings in the study are as follows: first, the rooms were in ratios of 1:5 or 10 square meters and 1:4 or 12.5 square meters. Light colored finishing materials were used for walls and ceilings. Floor materials ranged from polished concrete, vinyl and ceramic tiles, and wood planks. Two types of lighting used in these rooms were fluorescent lamps and compact fluorescent lamps, both a discharge type. The majority of illuminance levels in the rented rooms were in low conformance, reaching as low as 42 lux in a supposedly category of a lux level of 200-500 based on the IES Illuminance Category. Only one room met with a medium conformance due to the usage of two 20 watts fluorescent lamps. Second, the study focused on the physical effects and the students' perception of lighting of the room. Thirty-four out of 40 students experienced visual discomfort while 31 of 40 experienced eyestrain. Overall, 75 percent of students agreed that there was difficulty in performing tasks under these existing conditions. In contrary to the low light levels, 25 of 40 agreed or 62 percent agreed that there is sufficient lighting for the tasks performed. The study proved that there is a non-conformance of lighting levels in the boarding houses. Ninety percent of the studied boarding houses were in non-conformance to the standard lighting levels. The result of the questions related to these effects also reinforced the low conformance of the existing lighting conditions. Cost over efficiency was the primary consideration of landlords in creating the general lighting in the boarding houses with no additional task lighting present for tasks related to studying. With the ensuing outcome from the study, this may serve as a basis for formulation of lighting design for residential design.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Dwellings -- Lighting